(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Background: Road crashes not only place a heavy burden on national and regional economics but also on households. The cost of road traffic injuries is estimated roughly at 1% gross national product (GNP) in low-income countries, 1.5% in middle-income countries, and 2% in high income countries. The direct economic cost of global road crashes have been estimated at USD 518 billion with the cost in low income countries estimated at USD 65 billion exceeding the annual amount received in development assistance. The financial loss to India due to traffic accidents is estimated more than 12000 crore rupees annually. Objective: To evaluate the influences of associated factors in relation to Road Traffic Accidents (RTA) and to study association between mode of accident and pattern of injuries were the objective of our study. Methodology: This Prospective, descriptive and co-relational study on pattern of injuries in Road Traffic Accidents is carried out at Department of Forensic Medicine & Toxicology in Santosh Medical College and Hospital, Ghaziabad. There were 98 subjects of road traffic accidents. Result: The majority 59 (29.64%) fractures are observed in the lower extremity followed by upper extremity 39 (19.59%) and out of 98 victims of Road Traffic Accidents a maximum of 71(35.63%) fractures are found among pedestrian followed by two wheeler users. Conclusion: The current study illustrates the broad range of variables that contribute to traffic accidents. The epidemiological and medicolegal implications of traffic accidents in this region are also highlighted. The knowledge of the contributing elements to injuries and the suggestions offered in this study aid in averting such mishaps.